Pengaruh Persistensi Laba, Solvabilitas, dan Variabel Lainnya terhadap Kualitas Laba - Danibrata, Bagas (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to obtain empirical evidence about whether earnings persistence, solvency, liquidity, profitability, audit committee, and commissioner independence as independent variables have an influence on earnings quality as the dependent variable. This research used 210 data from 42 companies operating in the cyclical and non cyclical sectors that listed on Indonesian Stock Exchange for the period 2015 to 2022. The research method used in this research is the purposive sampling method in selecting samples and used multiple regression for the data analysis. The result of this research shows that independent variables earnings persistence and profitability affect earnings quality. While other independent variables earnings persistence, liquidity, audit committee, and independent commissioner have no effect toward earnings quality. Companies tend to do earnings management to keep their profit stable and to increase their profitability so which could end up lowering the quality of earnings